2013
DOI: 10.1002/xrs.2523
|View full text |Cite
|
Sign up to set email alerts
|

Determinations of low atomic number elements in real uranium oxide samples using vacuum chamber total reflection x-ray fluorescence

Abstract: Conditions for the total reflection x‐ray fluorescence (TXRF) analysis of real uranium samples for low atomic number elements using vacuum chamber TXRF spectrometer were optimized. It was observed that for analysis of low atomic number elements, almost complete removal of uranium matrix is required. Two certified reference materials of uranium containing trace elements in different concentrations were dissolved in minimum amount of high purity nitric acid. The uranium matrix from these solutions was separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The detector does not receive sufficient amounts of energy to distinguish significant concentrations of a certain element. In addition, background scatter tends to dominate the low energy peaks of light elements, making them hardly recognizable in an XRF spectrum [46,47]. While these drawbacks were mitigated in all scanners by large area silicon drift detectors (SDD), which improved detection of light elements, correlations and recovery rates for P, S, Al and Mg (atomic weight ≤16) were generally worse than for heavier elements.…”
Section: Xrf Performance For Light Elementsmentioning
confidence: 99%
“…The detector does not receive sufficient amounts of energy to distinguish significant concentrations of a certain element. In addition, background scatter tends to dominate the low energy peaks of light elements, making them hardly recognizable in an XRF spectrum [46,47]. While these drawbacks were mitigated in all scanners by large area silicon drift detectors (SDD), which improved detection of light elements, correlations and recovery rates for P, S, Al and Mg (atomic weight ≤16) were generally worse than for heavier elements.…”
Section: Xrf Performance For Light Elementsmentioning
confidence: 99%
“…The application of low‐energy tube excitation for the TXRF determination of low Z elements is reported in literature . As discussed in the preceding paragraphs, there is considerable improvement in the Fluorine DL by using 3.8 keV excitation compared with 5.41 keV SR excitation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the detection and the quantification of such elements by using different techniques have always been a challenging task . In the field of total reflection X‐ray fluorescence (TXRF) spectrometry, specialized spectrometers have been developed and applied for the determination of low Z elements in different sample matrices . Although TXRF analysis has offered a new dimension for trace element determination with detection limits for most of the elements comparable with those obtained by different, well‐established analytical techniques, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While analyzing the real uranium samples, we observed that even a very small amount of uranium present in the aqueous phase after solvent extraction, due to some solubility of TBP in aqueous phase, resulted in interference between the escape peak of U Mα with Al Kα and thereby erroneous results were obtained especially for trace Al determination. [14] This study indicated that a more rigorous separation of uranium is required for the determination of low-Z elements in it using vacuum chamber TXRF spectrometry. Recently, a low Z-high Z TXRF spectrometer was installed in our laboratory.…”
Section: +mentioning
confidence: 90%
“…These studies were carried out under bilateral collaborative programs between our institute and L. Eötvös University, Budapest, and later with Atominstitut, Vienna, respectively. [13,14] Tri-n-butyl phosphate (TBP) was used as the extracting agent for uranium in above studies. This organic extractant has very high affinity towards uranium, plutonium, thorium, zirconium, and so forth and hence is used frequently for their separation as well as purification.…”
Section: Introductionmentioning
confidence: 99%